2018
DOI: 10.1111/bjop.12367
|View full text |Cite
|
Sign up to set email alerts
|

The effects of presentation time on preference for curvature of real objects and meaningless novel patterns

Abstract: Objects with curved contours are generally preferred to sharp-angled ones. In this study, we aim to determine whether different presentation times influence this preference. We used images of real objects (experiment 1) and meaningless novel patterns (experiment 2). Participants had to select one of two images from a contour pair, curved and sharp-angled versions of the same object/pattern. With real objects, the preference for curved versions was greatest when presented for 84 ms, and it faded when participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 43 publications
4
27
0
Order By: Relevance
“…In Corradi et al (2018) we found similar effect sizes with real objects and meaningless patterns presented for short-medium times (84, 150, 300 ms), but different effect sizes for long times. The effect faded in the presentation time-until response with images of real objects as in Munar et al (2015), whereas it increased with meaningless patterns.…”
Section: Type Of Stimuli and Presentation Timesupporting
confidence: 73%
“…In Corradi et al (2018) we found similar effect sizes with real objects and meaningless patterns presented for short-medium times (84, 150, 300 ms), but different effect sizes for long times. The effect faded in the presentation time-until response with images of real objects as in Munar et al (2015), whereas it increased with meaningless patterns.…”
Section: Type Of Stimuli and Presentation Timesupporting
confidence: 73%
“…Using the same experimental paradigm, Gómez-Puerto et al (2017) found the same curvature advantage across Western and non-Western cultures. Corradi et al (2018) found that the approach to curvature was greatest when real objects were presented for 84 ms, but it faded when participants were given unlimited viewing time, as in Munar et al (2015). Corradi et al (2019) uncovered a remarkable breadth of variation in individual preferences, showing that participants who were highly sensitive to curvature in real objects were also highly sensitive to curvature in abstract shapes.…”
Section: Approachabilitymentioning
confidence: 93%
“…The idea of a preference for smooth curvature has a long history (for a review and historical perspective see Bertamini et al, 2015). This phenomenon has been documented for a variety of visual stimuli: familiar and unfamiliar objects (Bar & Neta, 2006;Bar & Neta, 2007;Corradi et al, 2019a;Corradi et al, 2019b) geometric or irregular abstract shapes, which prevent familiarity effects (Silvia & Barona, 2009;Bertamini et al, 2015) hand-drawn objects (Bertamini & Sinico, 2021) car design (Leder & Carbon, 2005) and complex interior design environments (Vartanian et al, 2013;Banaei et al, 2017;Ruta et al, 2019). The curvature effect has been replicated across a range of tasks, including explicit forced choice responses (''like''/''no like''), rating scales (Likert scale or visual attention scales-VAS) and selection procedure where participants chose one of two stimuli presented simultaneously (Gómez-Puerto, Munar & Nadal, 2016).…”
Section: Introductionmentioning
confidence: 99%